2016
DOI: 10.1589/jpts.28.1844
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between physical function, cognitive function, and health-related quality of life in elderly persons

Abstract: [Purpose] This study aimed to assess the quality of life of elderly people related to physical function, cognitive function, and health, and devised methods to enhance their health-related quality of life. [Subjects and Methods] This study was conducted from November 2014 to January 2015 in 140 people over 65 registered at welfare centers. Those with a functional psychological disorder or difficulty communicating were excluded. Data were collected for physical function, cognitive function, and health-related q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 7 publications
0
13
0
Order By: Relevance
“… 113 The growing number of smartphone devices in developing countries 114 can be used as a delivery tool while using a simple metronome app, such as WalkMate 115 or ListenMee, 116 which with proper medical guidance might allow curbing of motor deficits associated with aging. 117 We also suggest the use of rhythmic auditory cueing as an adjunct to other rehabilitation strategies, eg, assistive devices, 16 , 124 , 125 swimming, or other aquatic exercise regimes, 118 as it might enhance stability-associated quality of life 119 , 120 and rehabilitation progress by focusing on psychophysiological components.…”
Section: Discussionmentioning
confidence: 99%
“… 113 The growing number of smartphone devices in developing countries 114 can be used as a delivery tool while using a simple metronome app, such as WalkMate 115 or ListenMee, 116 which with proper medical guidance might allow curbing of motor deficits associated with aging. 117 We also suggest the use of rhythmic auditory cueing as an adjunct to other rehabilitation strategies, eg, assistive devices, 16 , 124 , 125 swimming, or other aquatic exercise regimes, 118 as it might enhance stability-associated quality of life 119 , 120 and rehabilitation progress by focusing on psychophysiological components.…”
Section: Discussionmentioning
confidence: 99%
“…← Click for updates doi: 10.7243/2056-9157- Other previous studies have shown that the aging process is often accompanied by diminished sleep quality and irregular sleep patterns [3][4][5], and that as age increases, physical HRQOL declines [6][7][8]. Furthermore, sleep problems were significantly correlated with chronic diseases, such as depression [5,9], heart diseases [5,9,10], arthritis [5,9,10], and lung diseases [9,10].…”
Section: Crossmarkmentioning
confidence: 99%
“…As the population grows older, it tends to suffer from various diseases; ranging from non-communicable diseases (12,13) to cognitive diseases (13)(14)(15) to various bodily functions disabilities such as vision or hearing loss, joints pain and so on (16,17). Also, older adults suffer from functional movements (18).…”
Section: Introductionmentioning
confidence: 99%